Film cooling effectiveness of a gas turbine blade with four rows of jet holes arranged staggered [electronic resources] - Aurel Lotius Bagu, 1989- (2012)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012